Brecht and critical theory : dialectics and contemporary aesthetics - Carney, Sean, 1970- (London ; New York : Routledge, 2005)
1. Brecht and language ## Marxism and rhetoric -- Brecht and postmodernism -- Verfremdungseffekt and unheimlich -- Psychoanalysis and class-consciousness -- Brecht and class -- Gestus, language, negation -- Marxism and science -- Lacanian gestus --##2. Dialectical images## Dialectic at a standstill -- Jetztzeit -- Dialectical images -- Modelbooks -- Kafka's gestus -- Trauerspiel -- Brechtian Trauerspiel -- Mourning as a socially symbolic act -- Hamlet -- "Marx" das Unheimliche? --##3. Brecht and myth##The structuralist activity -- The ruins of costume -- Brechtian photography -- Brecht and myth -- Numen and Punctum -- The maternal -- Fetishism -- Peaceable speech -- The art of living -- Seismology --##4. Brecht and narrative##An ethics of marxism -- The political unconscious -- Contradiction -- Allegory's violence: Life of Galileo -- Jameson, Frye, anagogy -- Menippean satire -- Dialogism and the dialectic -- Der Dreigroschenroman --##5. Brecht and tragedy##Dialectics in the theatre -- Negative dialectics -- Dialectical stereoscopy -- Adorno and Brecht -- Endgame -- Modern tragedy -- Brechtian tragedy.
Includes bibliographical references.
boek
Keywords: Brecht, Bertolt